Immune genes are primed for robust transcription by proximal long noncoding RNAs located in nuclear compartments - Fanucchi, Stephanie; Börner, Kathleen; Grimm, Dirk (Nature genetics, 2019)
This study shows that immune-related genes are primed for transcription by proximal lncRNAs. One such lncRNA, UMLILO, directs the WDR5-MLL1 complex to CXCL chemokine promoters, facilitating H3K4me3 deposition.
Published online: 10 December 2018
Gesehen am 10.07.2019